IMPORTANT INFORMATION ABOUT THE HISTORY OF THE GUZOR KINGDOM OF THE BUKHARA EMIRATE (BASED ON THE EXAMPLE OF GULSHANI'S BOOK “THE HISTORY OF HUMOYUN”) - Ergashev U.Q. (Western European Studies, 2024)
Muhammad Sadiqkhoja Gulshani`s work “History of Humayun” written in 1909 contains important information that illuminates the socio-political,economic and ethno-cultural situation of Khusar(Guzor) province of Bukhara Emirate in the early 20th century. In the article, the aspects of the history of the Khusar(Guzor) principality, which remain abstract until today, are presented, analyzed and prospective information is discussed.
Keywords: Muhammed; Sadiqkhodja Gulshani; Farsakh